APPLICATION OF WAVELET TRANSFORM FOR INTERNAL WAVE DETECTION IN SAR IMAGE - Yessy Arvelyna; Masaki Oshima (BRIN, 2004)
In this paper, wavelet transform based on dyadic scales and spatial location have been used for internal wave detection in SAR image. It performed by using multi resolution analysis of image for feature detection and image enhancement. Wavelet transform uses local analysis to analyze a shorter region in image in time and scale data allows precise information than time and frequency region analysis such as Fourier analysis. Internal wave is observed in SAR image by effect of Bragg scattering process in sea surface that represents the meso-scale feature of sea processes. SAR image data is used considering to the effectiveness of large scales area monitoring on near real time data. Internal waves were observed in ERS-1 per 2 SAR images data over Lombok Strait during 1996-2001 period using 2D Symlet analysis for the symmetric extension of data at the image boundaries, to prevent discontinuities by a periodic wrapping of data in fast algorithm and space-saving code. Lombok Strait is chosen as study area because this strait is a major passage of the flow from Pacific Ocean to Indonesian seas (ARLINDO) and passage of Indian Ocean Kelvin wave to Makassar Strait.